POMMS: Pre-operative misoprostol in myomectomy surgery: A randomised controlled pilot study. (September 2022) - Wetherell, Lima; Kathurusinghe, Shamitha; Dior, Uri; Szabo, Rebecca; Gilmartin, Christine; Polyakov, Alex; Ross, Vanessa; Dronavalli, Mithilesh; Catarina Ang, W.
Abstract: Objective: To assess the effect of pre-operative sublingual misoprostol on intra-operative blood loss in abdominal myomectomy as compared to placebo. Study design: Double-blind randomised controlled pilot study. A single tertiary Gynaecology Unit in Melbourne, Australia. Women ≥ 18 years old undergoing laparoscopic or open myomectomy. Women undergoing laparoscopic or open myomectomy for symptomatic uterine leiomyomas were randomised to pre-operative sublingual 400mcg misoprostol or placebo. Intra-operative blood loss was measured via accurate record keeping of the post-operative volume in the suction canister and weighed packs, minus any irrigation fluid used. Results: Intraoperative blood loss in the misoprostol treatment group was 306 ml ± 281 ml, compared to 325 ± 352 ml in the placebo group; P = 0.83. Fibroid volume was a consistent predictor of intra-operative blood loss. For each 1 ml increase in fibroid volume there is an increase in blood loss by 0.26 ml (95 % CI: 0.07 – 0.46). Conclusions: In this study, we found that there was no significant difference in blood loss between women who received and did not receive sublingual misoprostol before abdominal myomectomy. This is an exploratory study laying the foundation for further randomised clinical trials.